Carbon dots and fluorescein: The ideal FRET pair for the fabrication of a precise and fully reversible ammonia sensor - Hsu, C.-P.; Hejazi, Z.; Armagan, E.; Zhao, S.; Schmid, M.; Zhang, H.; Guo, H.; Weidenbacher, L.; Rossi, R.M.; Koebel, M.M.; Boesel, L.F.; Toncelli, C. (Sensors and actuators. B, Chemical, 2017)
[Display omitted] Monitoring of ammonia in the gas phase, a ubiquitous bulk chemical, is of paramount importance to ensure the safety of industrial workers. The present paper describes a solid-state optical ammonia sensor based on Förster resonance energy transfer (FRET) between narrowly dispersed blue-emitting carbon nanodots (CNDs) as FRET donor and fluorescein as FRET acceptor. The fluorophores were physically entrapped in a close to superhydrophobic sol–gel matrix, in turn deposited on a PVDF-HFP electrospun fiber membrane. The CNDs were synthesized via pyrolysis of ethylenediaminetetracetic acid (EDTA) in the presence of a hydrogen peroxide solution. X-ray photoelectron spectroscopy (XPS) confirmed a high surface coverage of hydrophilic groups, which is a result the addition of hydrogen peroxide in the reaction mixture. This translates into higher electrostatic interactions between ammonia and the fluorophores, in turn related to reduced FRET inter-distance between fluorescein and CNDs. If calibrated with respect to the fluorescein signal, the sensor shows a linear calibration with a remarkably low limit of detection, i.e. 110ppb, and adequate reproducibility up to six N2/NH3 cycles.